2016
DOI: 10.1002/2211-5463.12140
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral determination of phosphopantetheinylation specificity for carrier proteins in Mycobacterium tuberculosis

Abstract: Phosphopantetheinyl transferases ( PPT ases) are key elements in the modular syntheses performed by multienzyme systems such as polyketide synthases. PPT ases transfer phosphopantetheine derivatives from Coenzyme A to carrier proteins ( CP s), thus orchestrating substrate supply. We describe an efficient mass spectrometry‐based protocol for determining CP specificity for a particular PPT ase in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For this, we chose Drosophila melanogaster because of its conserved metabolic steps and genes and its versatile genetic tools. mtACP requires activation in order to function; the active holo form is generated by enzymatic transfer of a negatively charged 4′‐phosphopantetheine moiety to a conserved serine residue of the inactive apo form (Elovson & Vagelos, ; Jung et al , ; Fig A). For our study we manipulated mtacp , the Drosophila melanogaster gene encoding mtACP, containing Ser‐99, which is predicted to bind 4‐phosphopantetheine (Ragone et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…For this, we chose Drosophila melanogaster because of its conserved metabolic steps and genes and its versatile genetic tools. mtACP requires activation in order to function; the active holo form is generated by enzymatic transfer of a negatively charged 4′‐phosphopantetheine moiety to a conserved serine residue of the inactive apo form (Elovson & Vagelos, ; Jung et al , ; Fig A). For our study we manipulated mtacp , the Drosophila melanogaster gene encoding mtACP, containing Ser‐99, which is predicted to bind 4‐phosphopantetheine (Ragone et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the docking studies, a total of 205 top scoring molecules, named as P-1 to P-205, were procured from NCI/DTP and [10][11][12][13] and thus have carried out crystallization and enzyme characterization studies by using MBP-PptT fusion protein. 8,12,13 Additionally, these studies have also reported that cleavage of MBP tag results in signicant precipitation of PptT protein thereby making it difficult to work with native PptT. 10,12,13 Thus, we used MBP-PptT fusion protein for our activity assays and inhibition studies with M. tb AcpM as the substrate.…”
Section: Determination Of Inhibitory Potential Of Molecules Against Mmentioning
confidence: 99%
“…8,12,13 Additionally, these studies have also reported that cleavage of MBP tag results in signicant precipitation of PptT protein thereby making it difficult to work with native PptT. 10,12,13 Thus, we used MBP-PptT fusion protein for our activity assays and inhibition studies with M. tb AcpM as the substrate. In order to screen 205 molecules, we rst characterized PptT by carrying out the time kinetics as well as K m experiment with varying concentrations of CoA by using UPLC based method for precise quantication of apo AcpM and holo AcpM peaks.…”
Section: Determination Of Inhibitory Potential Of Molecules Against Mmentioning
confidence: 99%
See 2 more Smart Citations